2003
DOI: 10.1590/s0100-879x2003000900006
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and culture of umbilical vein mesenchymal stem cells

Abstract: Bone marrow contains a population of stem cells that can support hematopoiesis and can differentiate into different cell lines including adipocytes, osteocytes, chondrocytes, myocytes, astrocytes, and tenocytes. These cells have been denoted mesenchymal stem cells. In the present study we isolated a cell population derived from the endothelium and subendothelium of the umbilical cord vein which possesses morphological, immunophenotypical and cell differentiation characteristics similar to those of mesenchymal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
104
0
21

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(131 citation statements)
references
References 11 publications
6
104
0
21
Order By: Relevance
“…Furthermore, according to our observations, the untreated SLCs expressed neural markers and could differentiate into neural lineage after a shorter induction period as compared with NTERA-2 cells. To investigate mesodermal differentiation of SCLs, an osteogenic medium, containing dexamethasone, ascorbate-2-phosphate and b-glycerol phosphate, was used based on several reports and our previous experience (Covas et al 2003;Ahmadian Kia et al 2011;Sun and Ji 2012). Differentiation of SLCs toward osteocytes was confirmed by their mineralized matrix stained with Alizarin Red S. RT-PCR studies also indicated the expression of Ocn and Opn in differentiated SLCs, quite similar to induced rMSCs.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, according to our observations, the untreated SLCs expressed neural markers and could differentiate into neural lineage after a shorter induction period as compared with NTERA-2 cells. To investigate mesodermal differentiation of SCLs, an osteogenic medium, containing dexamethasone, ascorbate-2-phosphate and b-glycerol phosphate, was used based on several reports and our previous experience (Covas et al 2003;Ahmadian Kia et al 2011;Sun and Ji 2012). Differentiation of SLCs toward osteocytes was confirmed by their mineralized matrix stained with Alizarin Red S. RT-PCR studies also indicated the expression of Ocn and Opn in differentiated SLCs, quite similar to induced rMSCs.…”
Section: Discussionmentioning
confidence: 98%
“…Cell Culture and Reagents-Human MSCs from umbilical cord (19) were purchased from Inbiobank (Inbiomed, San Sebastian, Spain) and were cultured in low glucose DMEM (Lonza, Basel, Switzerland) supplemented with 10% MSC-qualified fetal calf serum (Promocell, Heidelberg, Germany). HBVPs were purchased from ScienCell Research Laboratories (Carlsbad, CA) and cultured in 2% fetal calf serum pericyte medium (ScienCell Research Laboratories).…”
Section: Methodsmentioning
confidence: 99%
“…A molécula CD73 pode ser expressa tanto em fibroblastos (2) quanto em CTM (30). Mas as moléculas CD90 e CD54 expressas em mais de 86% das células deste estudo são expressas nas CTM, não sendo expressas em fibroblastos e em células hematopoéticas (2,32,33). O resultado da caracterização fenotípica das células deste estudo está de acordo com as características de CTM propostas pelo Mesenchymal and Tissue Stem Cell Committee of the International Society for Cellular Therapy (34).…”
Section: Discussionunclassified